2014
DOI: 10.1373/clinchem.2013.215236
|View full text |Cite
|
Sign up to set email alerts
|

False Biomarker Discovery due to Reactivity of a Commercial ELISA for CUZD1 with Cancer Antigen CA125

Abstract: BACKGROUND By using proteomics and bioinformatics, we have previously identified a group of highly pancreas-specific proteins as candidate pancreatic ductal adenocarcinoma (PDAC) biomarkers. With the use of commercially available ELISAs, the performance of some of these candidates was initially evaluated in a relatively small serum cohort (n = 100 samples). This phase revealed that CUB and zona pellucida-like domains protein 1 (CUZD1) may represent a new, promising PDAC biomarker. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…The potential dangers of using unreliable and nonvalidated immunoassays in biomarker development have been addressed by Diamandis and coworkers (28,29 ). Among the suggestions made by these authors to minimize this possibility were to purchase such reagents from companies with a proven quality record, perform local validation, and report any identified problems.…”
Section: Robustnessmentioning
confidence: 99%
“…The potential dangers of using unreliable and nonvalidated immunoassays in biomarker development have been addressed by Diamandis and coworkers (28,29 ). Among the suggestions made by these authors to minimize this possibility were to purchase such reagents from companies with a proven quality record, perform local validation, and report any identified problems.…”
Section: Robustnessmentioning
confidence: 99%
“…For instance, Gutiérrez et al recently reported that an ELISA kit from USCN Life Sciences (Wuhan, China), which was designed to recognize human hemojuvelin, was not able to identify the analyte of interest but rather, an unknown protein, which was subsequently found to be the unrelated antigen, ferritin [7]. In our own recent report on a similar incident, we have shown that a kit purchased from the same company, designed to quantify CUB and Zona Pellucida-Like Domains Protein 1 (CUZD1), was unable to detect the analyte of interest but instead, the kit was quantifying the known ovarian cancer antigen, CA125 [8]. In the past, reports for unreliable ELISAs were mainly related to poor performance (e.g., precision) or possible cross-reactivities with other analyte(s).…”
Section: Translational Researchers Beware! Unreliable Commercial Immumentioning
confidence: 99%
“…We spent almost 2 years and approximately $500,000 to identify the antigen that the commercial assay for CUZD1 was measuring (CA125) [8]. Incidences like these also highlight additional possible harms, such as rejection of probably promising biomarkers, a situation that calls for a re-examination of such candidates by alternative technologies.…”
Section: Translational Researchers Beware! Unreliable Commercial Immumentioning
confidence: 99%
“…Leong et al demonstrated the importance of CUZD1 in cell growth and proliferation of a human ovarian cancer cell line and proposed a potential role of CUZD1 in chemotherapeutic resistance (61,62). Efforts have also been made to develop serum-based assays using CUZD1 as a biomarker for ovarian cancer and pancreatic cancer, however controversial reports support the need for additional studies (61,(63)(64)(65)(66)(67)(68)(69). Our recent work fills a gap in the body of knowledge surrounding CUZD1 by detailing the molecular signaling pathway of CUZD1-induced proliferation in mammary epithelial cells (51).…”
Section: Introductionmentioning
confidence: 99%